Paddle to Podium: Maximising sprint paddling velocity in elite female surfers. A three-year Olympic project - Parsonage, J.; MacDonald, L.; Gosney, S.; Denny, A.; Webster, H.; Minahan, C. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: In 2020, Teahupo`o was announced as the location for the Paris 2024 Olympic games. Teahupo`o is one of the largest waves of consequence in the world, and until 2022 was a wave not surfed by females in the modern era. This ignited a three-year performance strategy aimed at maximising sprint paddling velocity in elite female surfers, resulting in improved wave-riding performance at Paris 2024 and beyond. METHODS: A three phased approach to maximising sprint paddle velocity in elite female surfers was executed. Reliability (phase 1): The intra-session reliability of a 15-m sprint paddle assessments in ten elite female surfers was assessed. Characterisation (phase 2): Temporospatial analysis of sprint-paddling technique in thirty-one elite surfers (Female n=15, Male n=16), was undertaken, identifying characteristics of sprint paddling technique that commensurate with superior sprint-paddling velocity in a 15-m sprint paddle assessment. Technique Intervention (phase 3): Based on the aforementioned phases, a two-week paddle technique training intervention (10, one-hour sessions) focused on `reach` and `catch` was implemented to evaluate the magnitude of improvement in sprint-paddling velocity of an elite female surfer. RESULTS: The 15-m sprint paddling test demonstrated good to excellent intra-session reliability (ICC=0.76-0.94, CV%=1.55-2.52, TE=0.16-0.33), across 5, 10 and 15-m splits. Female surfers were significantly slower (p<0.0001) than their male counterparts across all splits and also demonstrated significantly shorter stroke length and propulsive distances (p<0.05) in both acceleration (ACC) and stroke maintenance (SM) phases. A longer pull distance in ACC was predictive of a faster 5-m sprint paddle time, in males but not females. The technique training intervention resulted in a superior time to ACC (pre: 5.84s at 8-9m, post: 3.52 at 4-5m). Furthermore, temporospatial analysis reported decreased stroke count (pre: 23 strokes, post: 20 stroke), increased stroke length in ACC [pre: right (R) =1.15 m left (L) =1.18 m, post: R=1.35m, L=1.31 m], and longer pull distance in ACC [pre: R=0.28m, L=0.29m, post: R=0.35m, L=0.33m]. However, no differences in sprint paddle velocity across 5, 10 and 15-m splits were reported. CONCLUSION:Paddle to Podium three-year strategy created a reliable measure of sprint paddle velocity in elite female surfers. Temporospatial results suggests that pull distance may play a crucial role for acceleration, and the absence of this within female surfers provided direction for phase 3 intervention. The performance improvements in temporospatial characteristics and time too ACC in an elite female surfer, is the first of its kind to be noted. The integrative and applied nature of this research project, resulted in biomechanists, physiologists, skill acquisition specialists and performance coaches uniting to deliver real world application and performance improvements.